Long-Term Nitrogen and Phosphorus Fertilization of Irrigated Corn - A. Schlegel; H. D. Bond (Kansas Agricultural Experiment Station Research Reports, 2018)
Long-term research shows that phosphorus (P) and nitrogen (N) fertilizer must be applied to optimize production of irrigated corn in western Kansas. In 2017, N applied alone increased yields by 70 bu/a, whereas P applied alone increased yields by less than 10 bu/a. Nitrogen and P applied together increased yields up to 130 bu/a. This is 10 bu/a less than the 10-year average, where N and P fertilization increased corn yields up to 140 bu/a. Application of 120 lb/a N (with highest P rate) produced 93% of maximum yield in 2017, which is similar to the 10-year average. Application of 80 instead of 40 lb P2O5/a increased average yields 10 bu/a. Average grain N content reached a maximum of 0.6 lb/bu while grain P content reached a maximum of 0.15 lb/bu (0.34 lb P2O5/bu). At the highest N and P rate, apparent fertilizer nitrogen recovery in the grain (AFNRg) was 42% and apparent fertilizer phosphorus recovery in the grain (AFPRg) was 61%.
Keywords: irrigated corn; nitrogen and fertilization of irrigated corn; long-term nitrogen and phosphorus fertilization